Nutrition content assessment of Arachis hypogaea L. samples grown in the Mediterranean region of Turkey - Turfan, Nezahat; Kurnaz, Aslı; Karataşlı, Muhammet; Özer, Tahsin; Turhan, Şeref (Turkish Science and Technology Publishing (TURSTEP), 2019)
A total of 42 Turkish peanuts (Arachis hypogaea L.) samples were analysed for their total free amino acid, β-carotene, lycopene, and flavonoid contents, and the total phenols, glucose, fructose and sucrose in the peanut samples were determined as nutrition aspects. The average values of the total free amino acid, beta-carotene, lycopene, glucose, fructose and sucrose were determined to be 14.4 Âµmol gâˆ’1, 14.4 Âµg (100 ml)âˆ’1, 14.4 Âµg (100 ml)âˆ’1, 1.07 mg gâˆ’1, 0.52 mg gâˆ’1 and 2.74 mg gâˆ’1, respectively. The results reveal that the consumption of Turkish peanut samples is safe and that they contain health-enhancing nutrients.
Keywords: nutrition; turkish peanuts; S; Agriculture (General); health-enhancing; turkey; Agriculture; adana; S1-972; 2. Zero hunger